2019
DOI: 10.29235/1561-8331-2019-55-3-377-384
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calcium and magnesium carbonate crystallization with sodium polyacrylate

Abstract: It is known that when water are used for technological purposes, in circulating water supply systems of enterprises as a coolant during continuous heating and cooling, the formation of insoluble precipitates, most often calcium carbonates, occurs on the walls of heat exchangers, which leads to a large number of problems, even production can be stopped for cleaning equipment. To prevent the formation of salts, it is necessary to use precipitation inhibitors. Sodium polyacrylate was investigated as a precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The influence of alkaline earth metal ions present in the extracted water on the crystallization of calcium carbonate is of practical importance for understanding the mechanism of sediment formation. Thus, the influence of the Mg 2+ ion concentration and temperature on the crystal structure of CaCO 3 was shown in [ 64 , 65 ]. It was found that the composition of polymorphic calcium carbonate formed during precipitation was determined by both the pH value and the duration of the crystallization process [ 64 ].…”
Section: The Main Causes Of Scale Deposits Formed In Technological Pr...mentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of alkaline earth metal ions present in the extracted water on the crystallization of calcium carbonate is of practical importance for understanding the mechanism of sediment formation. Thus, the influence of the Mg 2+ ion concentration and temperature on the crystal structure of CaCO 3 was shown in [ 64 , 65 ]. It was found that the composition of polymorphic calcium carbonate formed during precipitation was determined by both the pH value and the duration of the crystallization process [ 64 ].…”
Section: The Main Causes Of Scale Deposits Formed In Technological Pr...mentioning
confidence: 99%
“…Thus, the influence of the Mg 2+ ion concentration and temperature on the crystal structure of CaCO 3 was shown in [ 64 , 65 ]. It was found that the composition of polymorphic calcium carbonate formed during precipitation was determined by both the pH value and the duration of the crystallization process [ 64 ]. At t = 80 °C in the presence of Mg 2+ ions, the main polymorphic modifications of calcium carbonate were aragonite and magnesian calcite, and the content of aragonite increased as the duration of the crystallization process increased.…”
Section: The Main Causes Of Scale Deposits Formed In Technological Pr...mentioning
confidence: 99%
See 1 more Smart Citation